Pengaruh Event Lovely Toraja Terhadap Ekonomi Masyarakat di Kabupaten Toraja Utara - Lotim, Yohanis Bara; Damayanti, Maya (Magister Pembangunan Wilayah dan Kota,Undip, 2017)
North Toraja was the main tourism destination in South Sulawesi Province and Indonesia until economic crisis on 1997 and Bali bomb on 2002 hit Indonesia then decrease the number of visited tourists. The increase of the visited tourist since 2008 when this event initiated brings a research question How the impact of Lovely Toraja to the economic livelihood of the people in North Toraja Regency? This research aimed to analysis the impact of Lovely Toraja Event to the economic of community in Toraja Utara. Regarding its aim, this research can be classified as descriptive research with quantitative and qualitative approaches. Interview to the local government and cultural figures used as a tool of data collection to describe economic activities that growth within this event and then analyzed the results with exploration method. Questionnaires than spread to find labor absorption and change in the people income before the event, when there is no event occasion and when the event on occasion by tabulation method used as the analyzing tool. Results of the research showed that economic activities of the people that emerged of Lovely Toraja were accommodation, restaurants, tourist destination, travel agent, car rent, art community, sculpturer, crafter, webbing and weaving handicrafts, convection, and the home industry of food, street vendor, taxi bike, bentor, and Parkman. From the absorbance of labor known that the change about 46.64% and for the income of the business owner and the labor there isA significance increase about 92.12% and 69.20%. Thus, we can conclude that Lovely Toraja event brings significant impact to the economic of the community in North Toraja Regency.